EKSTRAKSI PEKTIN BUAH KELOR TUA DAN MUDA MENGGUNAKAN ASAM KLORIDA SECARA KERING PADA SUHU YANG BERBEDA - Khusnul Hatimah; Gatot Siswo Hutomo; Abdul Rahim (AGROTEKBIS : JURNAL ILMU PERTANIAN (e-journal), 2019)
Moringa fruit is contained one of soluble food fiber that is pectin. Pectin can be used as a thickening compound in the field of food. One type of acid solution that can extract pectin from the moringa fruit is hydrochloric acid. The research conducted in Agro-industry Laboratory, Faculty Agriculture of Tadulako University, Palu Central Sulawesi.The research conducted from June to November. The objective of the research is to obtain the best temperature on the extract pectin of morinnga dried using hydrochloric acid and producing the best physical or chemical quality of pectin. This research conducted using a Factorial Randomized Complete Random Design (RALF) which was repeated 3 times. Extraction temperature factors: 60 °C, 70 °C, 80 °C, 90 °C and maturity factor of fruit: young fruit, old fruit, so there are 24 units of experiments. The results showed that, the best physical and chemical quality pectin of dried extracted using hydrochloric acid at 60 °C included 1.76% fruit yield and 1.68% old fruit, 1.140% methoxyl contain, galacturonic 46.61% and clarity 93.68%.